The Effect of Tissue Fixation Duration on the Quality of Histopathological Examination Results at Sawerigading Palopo Regional General Hospital - Nurhilaliyah; Mujtahid Bin Abd. Kadir; Muhajirah; Muthahharah; Nirmala (Journal of Innovative and Creativity, 2026)
This study aimed to evaluate the effect of fixation duration on the quality of histopathological preparations of prostate tissue using Hematoxylin and Eosin (H&E) staining. A quantitative quasi-experimental design was employed using prostate tissue obtained from biopsy specimens at Sawerigading Palopo Regional General Hospital. Ten tissue samples were subjected to three different fixation durations 6 hours, 24 hours, and 48 hours resulting in 30 observational units. All specimens were fixed in 10% formalin and processed through standard histopathological procedures, including dehydration, clearing, embedding, sectioning, and H&E staining. Histological quality was assessed microscopically based on five parameters: staining quality, nuclear sharpness, cytoplasmic integrity, presence of artifacts, and clarity of histological structure. Data were analyzed using descriptive statistics and inferential tests, including normality testing and nonparametric correlation analysis. The results showed that fixation duration significantly affected histopathological quality. Specimens fixed for 6 hours demonstrated suboptimal morphology characterized by poor nuclear clarity and cytoplasmic integrity, whereas 24 hour fixation produced markedly improved histological features. The highest quality was observed in specimens fixed for 48 hours, showing optimal staining, clear nuclear detail, and minimal artifacts. Statistical analysis revealed a strong positive correlation between fixation duration and histological quality (p < 0.05). These findings indicate that fixation duration plays a critical role in determining the quality of prostate histopathological preparations, and a fixation period of 24–48 hours is recommended to obtain optimal diagnostic results.